ROLE-PLAY: A SIMULATED TEACHING TECHNIQUE IN PHYSIOLOGY - Khan, Huma Saeed; Sheikh, Naveen Siddique (Pakistan Journal of Physiology, 2021)
Background: Simulation is an artificial representation of a situation to facilitate learning without the risks inherent in a similar real-life experience. Role-play is one type of simulation that focuses attention on the interaction of students in scripted scenarios. In the process, students learn about that patient or given situation. This study was conducted with an aim to record the response of undergraduates to role-play of clinical scenarios and to have their feedback. Methods: Two clinical topics were selected from second-year MBBS Physiology syllabus and assigned to two groups of students, having 7 students each. Case scenarios were formulated; scripted and roles were divided among students. Role-play of each scenario was followed by a presentation on the pathophysiology. Student feedback was recorded and analysed. Results: Out of the 137, 56 (40.88%) were male and 81 (59.12%) were female students who participated in the study, 50.4% considered role-play alone as a useful learning tool whereas 94.9% agreed that if role-play is combined with a multimedia tool then it is useful for learning (?2=110.43, p<0.001). 95.9% said that role-play is enjoyable (?2= 114.07, p<0.001) and 97.1% said that it is a good technique to improve communication skills (?2= 121.46, p<0.001). Regarding future interest in more role-play scenarios, 56.9% of the study participants said they will be very interested. Conclusion: Hence, concluded that with careful planning and utilization of resources, role-play has the potential to be incorporated in the teaching of clinical scenarios to undergraduates to promote learning. Pak J Physiol 2021;17(4):46–50